Pengaruh Pendidikan Karakter Mahasiswa Terhadap Ketaatan Hukum (Studi Kasus di Kampus Universitas Bina Nusantara) - Irawan, Iwan (Humaniora, 2013)
In social life it is impossible apart from the laws and regulations that apply. Society must comply with and obey the law because the law observance will provide comfort and peace. The number of disputes in the community was triggered by the loss of the character of the Indonesian nation. The dispute led to violations of the law and cause discomfort. The study was conducted to determine the effect of character education to the students of law observance. The method used in this research is descriptive quantitative research methods. The number of samples in this study was 60 students and data analysis was performed by using regression analysis with SPSS. The results showed the characteristics of students who responded 53% of them turned out to have the value of honesty, 56% agreed to the value of mutual respect and 46% agreed for mutual cooperation. While the observance of law, students tend to obey the law for fear of sanctions and wants to be seen as a good person. Obedience to the law of the individual number is only 43%. Statistical test results also show that there is a relationship between the character and influence of the rule of law.